2006
DOI: 10.1002/polb.20878
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and morphological development of isotactic polypropylene blended with nanostructured polyhedral oligomeric silsesquioxane molecules

Abstract: The thermal properties and morphological development of isothermally crystallized isotactic polypropylene (iPP) blended with nanostructured polyhedral oligomeric silsesquioxane (POSS) molecules at very small loading of POSS were studied with differential scanning calorimeter (DSC), thermal gravimetric analysis, dynamic mechanical analysis, polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). The result of DSC indicated that the crystallization rate of iPP increases with the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Moreover, the increasing POSS mass% contents in polyolefin/POSS nanocomposites caused a further increase in the X c values. These results indicate that POSS particles may act as nucleating agents for the crystallization process of polyethylene or polypropylene matrices [20,25,31].…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the increasing POSS mass% contents in polyolefin/POSS nanocomposites caused a further increase in the X c values. These results indicate that POSS particles may act as nucleating agents for the crystallization process of polyethylene or polypropylene matrices [20,25,31].…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, the presence of POSS nanofillers clearly improved thermal stability of those materials [20,23,24]. However, it should be mentioned that the papers published to date covered mainly the properties of polyolefin/POSS nanocomposites which contained POSS molecules with relatively short alkyl chain substituents (from methyl to iso-octyl) [20][21][22][25][26][27][28][29][30]. Only few papers related to nanocomposites with long alkyl chain substituents (from n-octyl to n-octadecyl) on the T 8 POSS core [31,32] and most of those studies focused on PP/POSS [20-22, 25, 28-30] and LDPE/POSS [26,27,31,32] nanocomposites, while studies on HDPE/POSS nanocomposites were limited [33].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl substituted POSS, melt blended in isotactic polypropylene [67] and ethylene/propylene copolymers [68], restrict mobility and increase T g by a few degrees.…”
Section: Blended Systemsmentioning
confidence: 99%
“…Chen [19,20] also studied isothermal crystallization and morphology development in melt blended polyproplylene (PP)-octamethyl POSS nanocomposites. They found that the crystallization rate increased with increasing POSS content due to the aggregation of POSS nanocrystals.…”
Section: Introductionmentioning
confidence: 99%